Auditoría interna del área contable y presentación de los estados financieros de la cooperativa de servicios múltiples Frutos de Selva, Moyobamba – 2013 - Córdova Fernández, Denis (2015)
This research entitled is done in order to address and solve a local problem, the present study titled develops: "Internal audit of the accounting area and presentation of the financial statements of the Cooperative of Multiple Services Fruit Jungle, Moyobamba - 2013" , research originated from the need to respond to the question: What is the relationship between internal audit of the accounting area and the presentation of the financial statements of the Multiple Services Cooperative Fruit Jungle, Moyobamba - 2013 ?, unknown It is pretending to be resolved using the theories presented by Santillana (2013) and Apaza (2011), Therefore this research aimed to determine how internal audit is in accounting and how it relates to the presentation the financial statements of the Multiple Services Cooperative Forest fruits, Moyobamba - 2013, with the non-experimental methodology and research design has a descriptivecorrelational. To develop research sample consisted of 16 workers accounting and documentary heritage area that shows the economic performance of the Multiple Services Cooperative of Fruits of Forest. Also the technique used for the theoretical foundation was the documentary analysis and the study variables questionnaires and interview guides, which after being processed and analyzed by the researchers was used. For everything mentioned, and after the development of this research, reached the following conclusions: It has been shown that the processes of internal audit within the accounting area, often lack clear and well-defined objectives, why not have a logical time to be developed. Also, even when called to meeting those involved in the process, not reported in detail the documents and processes to investigate, why fear is generated within the staff. Everything pointed to internal audit determined that the accounting area is poor and has a direct connection with the presentation of the financial statements of the Multiple Services Cooperative Fruit Jungle, Moyobamba - 2013.